Orogenetische Ruinen. Simmels Alpen und die Eigendynamik von kulturellen Hyperobjekten - Niklas, Stefan (Simmel Studies)

(untitled) (Edizioni ETS, 2024)
This paper examines Georg Simmel’s philosophy to explore the Alps as “hyperobjects”—vast, interconnected entities shaped by natural and cultural dynamics. By integrating Simmel’s ideas on the autonomy of cultural objects with contemporary concerns of the Anthropocene, the Alps are reinterpreted as orogenetic ruins formed through geological and anthropogenic forces. The study critiques Simmel’s subjectivist view of landscapes, emphasizing their material and temporal independence while highlighting their relevance to ecological and cultural interconnections. This approach repositions Simmel’s insights within a planetary perspective, addressing the entanglements of nature and culture in the context of ecological crises and deep time processes.